Lipid raft-based membrane compartmentation of a plant transport protein expressed in Saccharomyces cerevisiae - Großmann, Guido (Eukaryotic cell, 2005)
The hexose-proton symporter HUP1 shows a spotty distribution in the plasma membrane of the green alga Chlorella kessleri. Chlorella cannot be transformed so far. To study the membrane localization of the HUP1 protein in detail, the symporter was fused to green fluorescent protein (GFP) and heterologously expressed in Saccharomyces cerevisiae and Schizosaccharomyces pombe. In these organisms, the HUP1 protein has previously been shown to be fully active. The GFP fusion protein was exclusively targeted to the plasma membranes of both types of fungal cells. In S. cerevisiae, it was distributed nonhomogenously and concentrated in spots resembling the patchy appearance observed previously for endogenous H+ symporters. It is documented that the Chlorella protein colocalizes with yeast proteins that are concentrated in 300-nm raft-based membrane compartments. On the other hand, it is completely excluded from the raft compartment housing the yeast H+/ATPase. As judged by their solubilities in Triton X-100, the HUP1 protein extracted from Chlorella and the GFP fusion protein extracted from S. cerevisiae are detergent-resistant raft proteins. S. cerevisiae mutants lacking the typical raft lipids ergosterol and sphingolipids showed a homogenous distribution of HUP1-GFP within the plasma membrane. In an ergosterol synthesis (erg6) mutant, the rate of glucose uptake was reduced to less than one-third that of corresponding wild-type cells. In S. pombe, the sterol-rich plasma membrane domains can be stained in vivo with filipin. Chlorella HUP1-GFP accumulated exactly in these domains. Altogether, it is demonstrated here that a plant membrane protein has the property of being concentrated in specific raft-based membrane compartments and that the information for its raft association is retained between even distantly related organisms.